Clinical profile and surgical outcomes of displaced supracondylar humeral fractures in children - Talukdar, M. Arifur Rahman; Hoque, M. Enamul; Hasan, M. Nahid; Wahid, A. H. M. Abdul; Hossain, M. Mobaraque; Hasan, M. Mahbub; Sohel, Sohelur Rahman (International Journal of Research in Orthopaedics, 2025)
Background: Supracondylar humeral fractures are the most common elbow injuries in children, frequently resulting from low-energy trauma such as falls on an outstretched hand. Displaced fractures often require surgical intervention due to risks of neurovascular compromise and functional impairment. Understanding patient demographics, fracture types and treatment outcomes is essential for optimizing care. The aim of this study was to assess the clinical profile and surgical outcomes of displaced supracondylar humeral fractures in children. Methods: This cross-sectional observational study was conducted at the Department of Orthopaedics, Shaheed Ziaur Rahman Medical College Hospital and Ibn Sina Diagnostic Centre, Bogura, Bangladesh from February 2025 to July 2025. Total 64 pediatric patients diagnosed with displaced supracondylar humeral fractures were enrolled in the study. Results: In this study, mean (±SD) age was 9.2±3.5 years and majority patients (65.6%) were male. Most injuries were sustained from falls on an outstretched hand (84.4%) and 62.5% were classified as Gartland type III fractures. Closed reduction with percutaneous pinning (CRPP) was performed in 81.3% of cases, while 18.7% underwent open reduction. According to Flynn’s criteria, 59.4% achieved excellent outcomes, 28.1% good, 9.4% fair and 3.1% poor. Complications were minimal, with only 15.6% experiencing issues such as pin tract infections, nerve palsy or malunion. Conclusions: Displaced supracondylar humeral fractures in children can be effectively managed with timely surgical intervention, particularly using CRPP. Most patients regain excellent to good elbow function, with a low rate of complications, reinforcing the safety and efficacy of current surgical protocols.